Tight control is a way of optimizing the treatment of patients with rheumatoid arthritis - Elvira Nikolayevna Otteva (Научно-практическая ревматология)
Objective: To evaluate the time course of changes in the symptoms of rheumatoid arthritis (RA) and its activity index during tight control in routine clinical practice. Subjects and methods. One hundred and twelve Khabarovsk outpatients with the valid (by the American College of Rheumatology (ACR) criteria) diagnosis of RA (88 females and 24 males; their mean age 37,8±1,9 years) were followed up. The patients were divided into 2 groups: 1) those who had been followed up once every 3-4 months by a rheumatologist in real clinical practice for 2 years; 2) those who were tightly controlled (estimation of the number of swollen and tender joints and general conditions, pain scores by the visual analogue 58 НАУЧНО-ПРАКТИЧЕСКАЯ РЕВМАТОЛОГИЯ, 2010, № 2, 51-58 ОРИГИНАЛЬНЫЕ ИССЛЕДОВАНИЯ scale, erythrocyte sedimentation rate, by calculating the disease activity score (DAS) 28 and functional index by the Health Assessment Questionnaire (HAQ)) by an investigating rheumatologist once monthly. The significance of differences between the groups was estimated by Student's t-test (a significant difference at p